Unraveling Gastric and Small Intestine Gastrointestinal Stromal Tumors: A Review of Our Current Knowledge - Panagiotis Eskitzis; Vasiliki Michou; Rodoula Theoti; Antonia Antoniou; Drosos Tsavlis; Doxakis Anestakis (Gastrointestinal Disorders)
Background: Gastrointestinal Stromal Tumors (GISTs) are characterized as round, well–defined mass lesions in the submucosal layer of the gastrointestinal (GI) tract. GISTs often present histological diversity and mutations in c-KIT and PDGFRA genes. Symptoms usually appear as abdominal pain, often accompanied by gastrointestinal bleeding or abdominal mass. The prognosis relies on tumor size, mitotic index, and different mutations, such as KIT mutations. There are a variety of diagnostic measures in the case of GISTs. However, it is important to note that ultrasound is the most common and reliable method for diagnosing gastric GISTs. The treatment methods followed vary from preoperative systemic therapy to surgical interventions. Depending on the type of GIST, professionals decide upon the best treatment plan for the patient. Objective: This review aims to inform the scientific community about the intricacies of gastric and small intestine GISTs to enhance understanding and improve patient management, with a particular focus on the importance of understanding and interpreting the unique microscopic histopathological findings of GISTs.